The Scale and Characteristics of Services Offshoring in the Visegrád Countries - Magdalena Myszkowska (Entrepreneurial Business and Economics Review, 2014)
The paper aims to outline the current position of V4’s as destinations for services offshoring activities, analyse the extent and patterns of service exports and service-based FDI, and to determine their potential as offshoring locations. The paper is divided into six sections. Following the introduction, the 2nd section provides the theoretical background and gives an overview of the definitions of services offshoring. The 3rd and 4th sections examine trade data in order to find evidence of enhanced offshoring-related service activities in V4’s. The 5th section studies the current and future position in the global services offshoring market of the CEECs. The final section contains research conclusions.